Employee Performance: Interaction Between Total Quality Management and Self Esteem Study in Soe Manufacturing Company - Veronica Christina; Novatiani, Ait; Sarumpaet, Tetty Lasniroha; Asikin, Bachtiar; Novianto, Robertus Ary (Jurusan Akuntansi Politeknik Negeri Bandung, 2024)
Good employee performance is very important for the company because it shows that the company's goals are achieved. This research was conducted to find solutions to the problems faced by one of the state-owned manufacturing companies. The condition factor, namely total quality management, which interacts with individual characteristics, namely self-esteem, is the solution variable in this study. Company employees are a population element, the sample is determined using probability sampling technique with a total sample of 87 employees. Moderated regression analysis is used to process data obtained with SPSS software. The results of the study found that self-esteem can be a quasi moderator of the effect of TQM on employee performance. The research findings are expected to be useful for improving employee performance and can be used by other parties who are interested in researching the fields of management accounting and behavioral accounting.